ChemInform Abstract: Regioselective Synthesis of 2‐Aryl‐4‐(arylethynyl)‐ and 2, 4‐Bis(arylethynyl)pyrrolo[2, 3‐d]pyrimidines. Issue 51 (December 2015) - Bucevicius, Jonas; Tumkevicius, Sigitas
Abstract: The approach is based on a comparative study of Sonogashira and Stille reactions of 2, 4‐dichloro‐7‐methylpyrrolo[2, 3‐d]pyrimidine with arylalkynes, (arylethynyl)tributylstannanes and aryltributylstannanes, respectively.